Co-creating academic career self-efficacy: exploring academic career segments, mediating and moderating influences in engineering education trajectory - Mahajan, Prashant (Frontiers in Education, 2024)
This study explores the dynamic relationship among different academic career stages within engineering education, using academic career self-efficacy (ACSE) one's belief in their academic ability, as the unitary construct. The purpose of this study was to examine the relationships between the academic career segments demonstrating self-efficacy at the beginning of career, during academic progression, and post-graduation completion, along with the mediating and moderating effects corresponding to the relationships.Quantitative survey was conducted on Indian recent engineering graduates. Data was collected from closed-ended questionnaire. Structural equation modeling was employed to analyze the relationships among academic career segments, mediation and the moderating impact of personal traits.Results: There were statistical significances among the relationships between academic career segments with each other. Notably, ACSE during academic progression emerged as a crucial mediator between entry-level ACSE and ACSE post-graduation completion. Furthermore, gender, social caste, engineering major, campus placement and engineering grade were identified as significant moderators for these relationships.Discussion: It sheds light on the significance of ACSE throughout diverse academic career segments enhancing career aspirations, engineering skills, and expressions and reflections that facilitate collaborative co-creation for engineering as a career. It contributes to the positive propagation of engineering education as an excellent and rewarding career choice.